Mothers' knowledge and understanding of their child's care at the time of cardiac surgery - Tallon, Mary (Curtin University, 2012)
The parents of young children who require cardiac surgery are often distraught because they fear their child may die or have long term health and developmental problems. Furthermore, parenting a seriously ill child often involves a great deal of uncertainty, due to a lack of knowledge and understanding about the child’s condition and subsequent care. Parents frequently report a sense of powerlessness which can be overwhelming. In this situation it is particularly difficult for them to process the medical and nursing information they are confronted with. There is some evidence to suggest that the experience of distress affects attention and memory. This is significant because children’s neurocognitive development may be affected by the condition and subsequent surgery and appropriate parental care is especially important at this time.This quantitative cross sectional study aimed to validate an instrument which was developed to measure maternal knowledge and understanding (MKU) at the time of heart surgery and to also explore the impact that stress, anxiety, depression, and social support may have on MKU. Mothers attending the Children’s Cardiac Centre at Princess Margaret Hospital for Children between Aug 2008 and April 2010 were recruited to participate. Validated instruments were used to measure levels of maternal stress, anxiety, depression and social support, while a consensual instrument was developed to measure MKU. Data were collected using a questionnaire. Descriptive, bivariate and multiple regression analysis were undertaken.Ninety one out of 146 mothers approached (61.4%) consented to participate in the study. The MKU scale (MKUS) demonstrated reasonable internal consistency (Cronbach’s Alpha .78). Twenty-nine per cent of mothers were experiencing significant stress, 28% anxiety and 22% depression at the time of questionnaire completion. Statistically significant relationships were found between the complexity of the child’s operation and maternal depression with mothers of children who were undergoing more complex procedures reporting higher levels of depression (p = 0.048). Financial strain was found to be associated with higher levels of maternal anxiety (p = 0.027).Analysis of variance confirmed a relationship between increased maternal anxiety and lower MKUS (p value= 0.036). While not directly associated with MKUS, maternal stress and depression were identified as mediators to MKUS through depression and anxiety. A significant relationship was found between mothers who did not see relatives at all, or often enough and lower MKUS (p value .005). Also mothers who reported they did not have someone to talk to outside the home recorded lower MKUS ( p value .005). A multiple regression model identified increased maternal anxiety, not seeing relatives often enough and no outside talks as independent predictors for lower MKU.This study examines the effects of maternal demographic factors, stress, anxiety and depression, and, social support on a mother’s understanding and capacity to relate this information to the care of her child at the time of cardiac surgery. The findings in this study call for more research to further develop the MKUS for potential adaptation across wider range of settings where care is provided for the seriously ill children in hospital. Examination of this research question also highlights the importance of the care of the child in the context of family and community. These findings challenge paediatric nurses to further contemplate the frameworks that support the family-centred care framework.This research invites paediatric nurses, in addition to maternal attachment, to bring more formally consideration for the influences of bioecological embedding and the family’s physical, psychological and social capital to acute paediatric nursing practice. Formal consideration for these factors within nurse-family relationship building and communication could potentially bring more timely attention to factors that influence a mother’s understanding of her child’s condition and care in the acute paediatric hospital setting.